Status of pulse milling processes and technologies: A review. Issue 10 (3rd July 2018) - Vishwakarma, Rajesh Kumar; Shivhare, Uma Shanker; Gupta, Ram Kishore; Yadav, Deep Narayan; Jaiswal, Arvind; Prasad, Priyanka
ABSTRACT: Pulses are essential component of the human diet in the underdeveloped and the developing countries. Pulse milling mainly focuses on complete removal of the hull with minimum generation of powder, broken, and in certain cases dehulled split formation. Physical and mechanical properties of different pulses are described and their role in dehulling is discussed in this review. The review discusses nature of gums that binds hull and cotyledons together and their effect on milling characteristics. Pitting operation is performed for all pulses prior to the pretreatment for better dehulling. Various pretreatment processes (soaking, edible oils, chemicals, enzymes, hydrothermal) developed to loosen the bond are examined for their dehulling efficacy from commercial application viewpoint. Dependence of dehulling characteristics of different pulses on size, shape, variety, grain hardness, and moisture content are discussed. Most of the machines developed for pulses dehulling in India are abrasion based emery-cylinder concave system. The studies done for optimization of different pretreatment process conditions are also reviewed. The losses taking place in the form of broken and powder during pulse milling are described. Methods for performance evaluation of the pulse dehulling system are reviewed and expressions are suggested for proper evaluation. This review gives complete overview of the processes and technological status of pulse milling in present context.